Daughters of the Anglican clergy: religion, gender and identity in Victorian England - Yamaguchi, Midori (Genders and sexualities in history series, 2014)
"In Victorian times, when the existence of a 'family enterprise' was still prominent, a father's occupation had an immense impact on the lives of middle-class women. It shaped their lives and affected the construction of their identity, especially as middle-class women had few qualifications of their own. As the Church of England steered its way through the expansion of Nonconformist sects, the threats of disestablishment, the spread of 'intellectual doubt', and the agricultural depression, the lives of the inhabitants of individual parsonages were influenced by the Church's reactions to these crises. The circumstances of the daughters of its clerics would, in turn, come to shape Church attitudes towards women's causes; the emotional tie between father and daughter often underpinned such institutional views. Midori Yamaguchi reveals links between lives in Victorian parsonages, women's educational reform, strategies of the Church of England, the growth of Victorian charity, the expansion of women's occupations and the development of feminism"--